2019
DOI: 10.1029/2018ja026134
|View full text |Cite
|
Sign up to set email alerts
|

Global‐Scale ULF Waves Associated With SSC Accelerate Magnetospheric Ultrarelativistic Electrons

Abstract: We study electron behavior in the outer radiation belts during the 16 July 2017 storm sudden commencement (SSC), in which prompt intensification of ultrarelativistic electron fluxes was observed at around L = 4.8 by Van Allen Probe B immediately after an interplanetary shock. The electron fluxes in multiple energy channels show clear oscillations in the Pc5 frequency range, although the oscillation characteristics are quite different in different energy channels. At energies above ∼1 MeV, the oscillation perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 59 publications
0
73
1
Order By: Relevance
“…Furthermore, in situ measurements have shown that there can be drift resonant interactions with corresponding PSD enhancement of particles by these low‐frequency waves. For instance, Hao et al () in this collection show the outer belt ultrarelativistic electron enhancement (from Relativistic Electron‐Proton Telescope (REPT) measurements) associated with the storm sudden commencement of the 16 July 2017 geomagnetic storm. These authors explain and reproduce the prompt electron acceleration response (from 2 to 3.4 MeV in less than 1 hr) to the shock‐induced ULF wave in the Pc5 frequency range using a generalized drift resonance theory.…”
Section: Particle Acceleration and Transport In The Inner And Outer Zmentioning
confidence: 99%
“…Furthermore, in situ measurements have shown that there can be drift resonant interactions with corresponding PSD enhancement of particles by these low‐frequency waves. For instance, Hao et al () in this collection show the outer belt ultrarelativistic electron enhancement (from Relativistic Electron‐Proton Telescope (REPT) measurements) associated with the storm sudden commencement of the 16 July 2017 geomagnetic storm. These authors explain and reproduce the prompt electron acceleration response (from 2 to 3.4 MeV in less than 1 hr) to the shock‐induced ULF wave in the Pc5 frequency range using a generalized drift resonance theory.…”
Section: Particle Acceleration and Transport In The Inner And Outer Zmentioning
confidence: 99%
“…These ULF waves, especially their poloidal-mode branches with electric field oscillations in the azimuthal direction, can accelerate or decelerate charged particles as they follow magnetic gradient and/or curvature drift orbits around Earth. In other words, this process provides an important energy source for particle acceleration and transportation in the Van Allen radiation belts Liu et al, 2016;Mann et al, 2016;Sarris et al, 2017;Hao et al, 2019;Degeling et al, 2019). This resonant process is called drift resonance (Southwood and Kivelson, 1981;Southwood and Kivelson, 1982;, during which particles can have a net energy gain (or loss, depending on the phase difference) from the ULF waves.…”
Section: Introductionmentioning
confidence: 99%
“…The simulated energization and drift phase bunching due to the bipolar electric field that accompanies the dayside compression are found to be consistent with VAP observations, reproducing the energy-dependent drift echoes and observed spectra. It is clear from direct comparison of simulated and observed drift echoes that the energization is prompt, dominated by the initial bipolar electric field impulse rather than continuous acceleration by the lower-amplitude damped ULF oscillations, as suggested by Hao et al (2019). Thus, the mechanism proposed by Li et al (1993) for the March 1991 injection holds for much weaker events, commonly seen in the VAPs era.…”
Section: Discussionmentioning
confidence: 87%
“…An oscillatory electric field typically follows the primary bipolar electric field impulse due to the magnetopause compression as seen in Figure 2. Hao et al (2019) showed that a persistent m = 1 oscillation can also be effective at accelerating lower-energy electrons when a finite damping time allows for interaction of drift resonant electrons with the ULF wave over multiple drift periods. Hao et al (2019) also show in their supporting information Figure S2 that an idealized dipolar azimuthal electric field impulse only, without ringing ULF oscillations, can produce the observed acceleration at higher energies as modeled here with direct MHD test particle simulations.…”
Section: Discussionmentioning
confidence: 99%